Innovating at the top : how global CEOs drive innovation for growth and profit - Berger, Roland , 1938- (INSEAD business press series, 2009)
"Innovating at the Top presents revealing interviews with CEOs at nine highly innovative international corporations - Bosch, Genentech, Infosys, Nokia, Research in Motion, SAP, 3M, Toyota, and Unilever - to gain their views how to encourage and support innovation." "When CEOs across three continents express many similar opinions about stimulating innovation, it is clear there are fundamental principles and methods all CEOs should explore to spin up the flywheel of innovation." "Innovating at the Top distills 10 Key Innovation Drivers from insightful CEO recommendations and advice. These innovation management practices can help every CEO consider proven ways to raise the probability a company can reach and sustain stronger innovative performance." "Soumitra Dutta, the Roland Berger Chaired Professor in Business and Technology and Dean of External Relations at INSEAD, researches the interrelationships among innovation, technology, and organizational design. A fellow of the World Economic Forum, he has won several awards for research and pedagogy."--BOOK JACKET